The role of park attributes in visitor satisfaction: evidence from Minneriya National Park in Sri Lanka - Ruwan Ranasinghe; Udeshika Kumudulali; Amaya Kaumadi Ranaweera (Goodwood Publishing, 2019)
Purpose: This study was to explore and recognize visitor satisfaction on Minneriya national park, and this evaluation was to define the gaps for future national park studies in Sri Lanka. Research Methodology: Quantitative research design was used for the study. A self-administered questionnaire was distributed to 180 foreign visitors and 180 local visitors. Purposive sampling tool was used in the study. SmartPLS was used as a tool to run the proposed theoretical model. Results: Destination image impacts of tourist satisfaction show that someone visiting a destination is strongly linked to the image of the tourist destination visited, particularly for those who have visited several times. Overall findings highlighted that all the hypotheses were accepted Limitations: Tourists’ satisfaction on park attributes is not to be the only factor effects on visitor satisfaction. Contribution: The study findings also provide guidelines for practitioners within the service sector to undertake the result and to adapt it to assessing and enhancing performance in national parks in Sri Lanka Keywords: Park attributes, Visitor satisfaction, Travel motivation, Destination image